UJI KANDUNGAN TANIN DAUN SALAM (SIZYGIUM POLYANTHUM) MENGGUNAKAN BERBAGAI KONSENTRASI ETANOL - Soraya, Soraya (Politeknik Kementerian Kesehatan Banjarmasin, 2023)
Bay leaf extract contains alkaloids, flavonoids, saponins, steroids, terpenoids, essential oils, citral, and eugenol, tannins. Tannins are known to be active compounds of secondary metabolites which have various benefits in medicine and the food industry, because they have antioxidant, antibacterial, anti-diarrhea and antitumor properties. The bay leaf sample used in this study came from the Banjarbaru area, South Kalimantan, Indonesia. This research was conducted in several stages, namely raw material processing, extract preparation, extract separation and tannin content testing. Product analysis uses the UV-Vis Spectrophotometry method with K₄Fe₆ and FeCl₃ solutions and gallic acid indicator. With an ethanol concentration of 96%, the highest tannin content was obtained, namely 0,854 mg/mL.And the lowest tannin content was obtained on ethanol 60%, namely 0,188 mg/mL